Structure Activity Relationship Study and Recent Advances in the Design and Synthesis about Linear Antimicrobial Peptides - Lee, K-H. (Current Medicinal Chemistry - Anti-Infective Agents, 2002)
Numerous defense peptides (cationic antimicrobial peptides) were isolated from eukaryotic systems and their functions were studied. In spite of size, primary sequences, and structures, most of them shared common features. They preferentially bind to lipid membranes of microbes and increase permeability of lipid membranes as a primary mode of action. The characteristics of cationic antimicrobial peptide different from conventional antibiotics make themselves a candidate for novel antimicrobial agents. In this review, we will provide a general overview of linear antimicrobial peptides with emphasis on aspects such as structure, biological mode, and structural parameters for activity and selectivity in vitro. And this review will focus on recent design and synthesis of novel peptide analogs with enhanced stability and selectivity.
Keywords: cationic antimicrobial